2019
DOI: 10.31227/osf.io/tfbnm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pengaruh Motivasi, Tingkat Kesejahteraan Dan Kedisiplinan Kerja Terhadap Etos Kerja Karyawan Pada PT. Bakti persada perkasa Makassar

Abstract: Tujuan dilakukannya penelitian ini adalah untuk menganalisis dan menguji pengaruh motivasi, tingkat kesejahteraan dan kedisiplinan, terhadap etos kerja karyawan pada PT. Bakti Persada Perkasa Makassar baik secara parsial maupun secara simultan. Penelitian ini merupakan penelitian explanatory research dengan menggunakan pendekatan kuantitatif. Ukuran besarnya sampel dalam penelitian ini adalah 72 responden yang juga merupakan jumlah besarnya populasi, jadi penentuan sampel menggunakan metode sensus. Adapun te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
2
1
Order By: Relevance
“…In research by Zagoto (2020), it was stated that motivation significantly influences work ethic. This is different from the research conducted by Lisna et al (2019), which shows the motivational variable does not positively affect the work ethic variable. Research gaps are also found in research by Afandi (2021).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In research by Zagoto (2020), it was stated that motivation significantly influences work ethic. This is different from the research conducted by Lisna et al (2019), which shows the motivational variable does not positively affect the work ethic variable. Research gaps are also found in research by Afandi (2021).…”
Section: Introductioncontrasting
confidence: 99%
“…Regarding the gap research that underlies this research, there are several previous researchers whose conclusions conflict with theory, but the results are different in this research with the same variables. These findings include that motivation has no positive and insignificant effect on work ethic (Lisna et al, 2019), whereas in this research motivation has a positive effect on work ethic. The results of this research are in line with research by Zagoto (2020).…”
Section: Hypothesis Testingcontrasting
confidence: 63%
“…Fina, Nadia Pengaruh Sosial Budaya, Latar Belakang Pendidikan Selain itu, penelitian dari Lisna, Syahruddin, Muhammad Fachmi (2019) menyatakan bahwa motivasi kerja bepengaruh signifikan terhadap etos kerja (Lisna et al, 2019).…”
Section: Pendahuluanunclassified
“…The scholarly work conducted by Lisna et al (2019) elucidates the intricate interplay between work discipline and work ethic. Their findings reveal a noteworthy and affirmative correlation between work ethic and work discipline among employees.…”
Section: Introductionmentioning
confidence: 99%